Relative Contributions of Innate and Acquired Host Responses to Bacterial Control and Arthritis Development in Lyme Disease - Wang, Xiaohui (American Society for Microbiology, 2005)
TLR2(−/−)/scid double-mutant mice were infected with B. burgdorferi to assess the relative importance of acquired and innate host defenses. Although spirochete levels at 4 weeks were lower in TLR2(−/−) mice than in TLR2(−/−)/scid mice, the increased arthritis severity of TLR2 (Toll-like receptor 2)-deficient mice was reduced by the presence of the scid mutation.